Geospatial data model of enterprise GIS for Kulai Municipal Council - Mohamad Ghazali, Muhammad Suhaib (2013)
The implementation and development of GIS as a tool for decision making by government agencies and local authority has grown rapidly. However, the GIS implementation by government agencies and local authority is not implementing Enterprise GIS among department and division that involved with GIS development in MPKu. Every government agencies and local authority have developed GIS by using their own specification, standard and purpose of planning and development. Because of this, geospatial data repository that has been located at each agency can’t be shared easily. Thus the implementation of Enterprise GIS is one of solution to provide a platform for geospatial data sharing. To enable the sharing of geospatial data, geospatial data standards can be crucial. This research was conducted by taking two departments in Kulai Municipal Council (MPKu) which are Property Valuation and Management Department and Urban Planning Department as a case study and only focuses on development of geospatial data model for MPKu. To develop this geospatial data model, the researcher has identified and gets requirements from both departments. From these requirements, geospatial data model for MPKu is developing by referring to chosen standard which is Malaysia Standard Geographic Information/Geomatics – Features and Attributes Codes. The result from this research have been evaluate by using several methods which are doing a demonstration and also doing a user acceptance test. The result also have been evaluate by a chosen GIS expert.